(untitled) (Bangladesh Journal of Medicine, 2021)
COVID-19 caused by SARS COV-2 is a major threat to man kinds. Rapid identification of cases and isolation are vital for containments of rapidly spreading disease.Clinical data on COVID 19 in Bangladesh is lessThe objectives of the study were to evaluate the Demographic profile of Corvid 19 positive Bangladeshi patients and also to see their clinical outcome within defined period. We conducted a retrospective descriptive study on epidemiological & clinical profile along with short term treatment outcomes of 729 COVID 19 patients from COVID dedicated unit including Ward/Cabin, HDU & ICU of Evercare Hospitals Dhaka during the period of 1st May June to 31st October 2020 (6 months) Total 729 COVID-19 cases were enrolled after getting the result positive for RT-PCR. After collection, data were analyzed to show demographic profile of patients and their outcome after treatment.Among 729 cases, 453 (62%) were male and 276 (38%) were female. The most prevalent affected age groups were 50-64 (32%) . Patients in 15-29 years age group, 52 (10%) in 30- 49 years, 218 (29%). in 50- 64 years of age 247(32%) and in 65 above of age 212(29% Mean age is 52.2±2. Among the total admitted cases in different facilities only 79 patient expired .among them 48 patients was male and 31 was female of different age group. Bangladesh J Medicine January 2021; 32(1) : 25-30